Analysis of Emotional Intelligence and Learning Outcomes of Students in Science Learning - Gunawan Gunawan; Agus Ramdani; Saprizal Hadisaputra (Postgraduate, University of Mataram, 2022)
Emotional intelligence is one indicator of academic success, where students who have high emotional intelligence will be active and work better in their groups. Emotional intelligence is very necessary for understanding the lesson delivered by the teacher. This study aims to analyze the effect of the learning model on student learning outcomes and analyze the influence of emotional intelligence on student learning outcomes. This study uses 3 learning models, namely, Project-Based Learning (PBL), guided inquiry, and conventional. This study employs a quasi-experimental method known as